Pentingnya Profesi Wirausaha di Indonesia - Z. Heflin Frinces (Universitas Negeri Yogyakarta, 2010)
Entrepreneur is a subject that has been widely discussed because it has long been recognized to have played a significant role in not only increasing ones income but more than that it has been noted to improve peoples quality of life and nations prosperity as it has been shown in the experiences of many developed and developing countries such as Malaysia, Singapore, Taiwan, Hongkong, Japan, South Korea, the United States of America, and most of European countries. At present governments of those countries are providing a great deals of attention and efforts to increase number of entrepreneurs in these countries including Indonesian Government. As noted in this article that it requires at least 2% of a countrys population are entrepreneurs to reach a prosperity level of a country and to increase purchasing power of the population. Those experiences have led many experts and governments in many countries are very keen to study nature and characteristics of entrepreneurs and looking for right answers to questions as to why is it so important to be an entrepreneur?, why society need entrepreneur?, and what are the elements of becoming successful entrepreneurs?. Answers to these questions will be found in this article. But what interest to some quarters to note is that (1) successful entrepreneur are characterized as to have strong willingness to take risk and to undertake strategic changes as required to make progress, and (2) there are specific skills such as skills to produce products and services, to market, and to calculate cost and profit quickly required by any successful entrepreneurs.